Global Workspace Theory and Sensorimotor Theory Unified by Predictive Processing. - Jęczmińska, Kinga (Journal of Consciousness Studies, 2017)
Degenaar and Keijzer (2009) claim that workspace theories and sensorimotor theories are complementary rather than competitive, so their combination has higher explanatory power than either approach on its own. I focus on the global workspace theory developed by Baars and the sensorimotor theory developed by O'Regan and Noe. The first theory analyses how consciousness emerges from dynamic interactions between unconscious processes. The second theory emphasizes the organism-world interaction, out of which conscious experience arises. I argue that the two theories may be combined together with predictive processing in its version developed by Clark. The predictive processing framework explains processes that underlie conscious and unconscious experience on a more fine-grained level than sensorimotor theory. Likewise, conscious processes on the highest level in the multi-level structure accounted for by predictive processing may be identified with the global workspace.